2018
DOI: 10.3390/ijerph15050932
|View full text |Cite
|
Sign up to set email alerts
|

Smelting Remains a Public Health Risk Nearly a Century Later: A Case Study in Pueblo, Colorado, USA

Abstract: Pueblo, Colorado has a long history of smelting activities, and recent studies raised concerns about lead exposure. This study tested 240 children in Pueblo for blood lead levels (BLLs) and found a significant association between distance from old smelters and children BLLs. Around 7.5% of Pueblo children had BLLs above the Centers for Disease Control and Prevention reference level of 5 µg/dL for elevated BLL, and 18.3% had BLLs between 3.3–4.9 µg/dL. Out of the 36 children who lived near former smelters, 13.9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Shen, et al, 26 studied the gene distribution of the ALAD isozyme phenotypes in 229 children aged 6-10 years who live within a community in which a large smelter is located; they found ALAD1/1 (92%), ALAD1/2 (8%), and ALAD2/2 (0%). Diawara, et al, 27 reported that among 231 children who lived next to smelting activities in Pueblo, Colorado, the United State of America, 94.4% of children had ALAD1/1, 5.6% had ALAD1/2 polymorphisms, and none had ALAD1/1 polymorphism.…”
Section: Kesmas: Jurnal Kesehatan Masyarakat Nasionalmentioning
confidence: 99%
“…Shen, et al, 26 studied the gene distribution of the ALAD isozyme phenotypes in 229 children aged 6-10 years who live within a community in which a large smelter is located; they found ALAD1/1 (92%), ALAD1/2 (8%), and ALAD2/2 (0%). Diawara, et al, 27 reported that among 231 children who lived next to smelting activities in Pueblo, Colorado, the United State of America, 94.4% of children had ALAD1/1, 5.6% had ALAD1/2 polymorphisms, and none had ALAD1/1 polymorphism.…”
Section: Kesmas: Jurnal Kesehatan Masyarakat Nasionalmentioning
confidence: 99%
“…With the growing demand for Pb and Zn resources in China, the environmental problems arising from the Pb/Zn smelting process cannot be ignored. During the smelting of Pb/Zn minerals, a large amount of waste water, waste gas and solid waste is generated; if improperly treated or discharged, it causes soil heavy metal pollution, and ultimately results in harm to human health through the food chain [6,14,[22][23][24]. At present, studies on the environmental release of Pb/Zn during smelting in China are insufficient, and the environmental release and distribution of Pb/Zn at the provincial level is unclear.…”
Section: Introductionmentioning
confidence: 99%